ETNOGRAFI WAKTU PERKOTAAN UNTUK MEMBACA PERLAWANAN RITMIK KOMUNITAS MARJINAL DALAM RUANG KOTA MAKASSAR - Djufri, Djufri (JCI Publisher, 2025)
This study explores how marginalized communities in Makassar construct and sustain their life rhythms amidst the temporal pressures shaped by infrastructure systems, mobility regimes, and urban development logics. Employing a space- and time-based urban ethnographic approach, the research traces residents’ daily tactics, rhythmic narratives, and spatial practices in navigating mobility exclusion and the accelerating, non-inclusive urban pace. Field findings reveal that residents engage in various forms of micro-resistance—such as adjusting selling hours, utilizing interstitial moments in urban space, and cultivating social rhythms that diverge from technocratic logics. Within temporalities not governed by state or capital, urban spaces are collectively reproduced from below, positioning spatial production as a bottom-up process rather than a top-down imposition. The study contributes theoretically by advancing Lefebvre’s rhythmanalysis, Urry’s notion of differential mobility, and Gandy’s political ecology of infrastructure within the context of Global South cities. By foregrounding time as a critical analytical lens, the research expands our understanding of how power operates temporally in urban life, and how residents negotiate this power through their everyday rhythms. Ultimately, this research offers a new perspective for interpreting urban dynamics—not only through spatiality but also through socially produced temporalities.